Comparison of upfront haploidentical hematopoietic stem cell transplantation and salvage haploidentical hematopoietic stem cell transplantation after immunosuppressive therapy in children with acquired severe aplastic anemia - a multicenter study - Luo, Danqi; Qu, Yuhua; Wang, Dao; Zhang, Benshan; Sun, Ming; Xiong, Hao; Lu, Jun; Yang, Rui; Zhao, Mingyi; Liu, Haiyan; Jiang, Hua (Frontiers in Immunology, 2024)
Background For children with severe aplastic anemia, if the first immunosuppressive therapy (IST) fails, it is not recommended to choose a second IST. Therefore, for patients without matched sibling donor (MSD) and matched unrelated donor (MUD), haploidentical hematopoietic stem cell transplantation (Haplo-HSCT) can be chosen as a salvage treatment. This article aims to explore the comparison between upfront Haplo-HSCT and salvage Haplo-HSCT after IST. Methods 29 patients received salvage Haplo-HSCT, and 50 patients received upfront Haplo-HSCT. The two groups received Bu (Busulfan, 3.2mg/kg/d*2d on days -9 to-8), CY (Cyclophosphamide, 60mg/kg/d*2d on days -4 to-3), Flu (fludarabine, 40mg/m2/d*5d on days -9 to -5) and rabbit ATG (Anti-thymocyte globulin, total dose 10mg/kg divided into days -4 to -2). Results The OS of the salvage Haplo-HSCT group showed no difference to the upfront Haplo-HSCT group (80.2 ± 8.0% vs. 88.7 ± 4.8%, p=0.37). The FFS of the salvage Haplo-HSCT group also showed no difference to the frontline Haplo-HSCT group (75 ± 8.2% vs. 84.9 ± 5.3%, p=0.27). There was no significant difference in the incidence of other complications after transplantation between the two groups, except for thrombotic microangiopathy (TMA). In the grouping analysis by graft source, the incidence of II-IV aGVHD in patients using PBSC ± BM+UCB was lower than that in the PBSC ± BM group (p=0.010) Conclusion Upfront Haplo-HSCT and salvage Haplo-HSCT after IST in children with acquired severe aplastic anemia have similar survival outcomes. However, the risk of TMA increases after salvage Haplo-HSCT. This article provides some reference value for the treatment selection of patients. In addition, co-transplantation of umbilical cord blood may reduce the incidence of GVHD.